Aspek Hukum Jual Beli Smartphone Dengan IMEI Tidak Terdaftar Pada Central Equipment Identity Register (CEIR) Kementerian Perindustrian - Amelia Wulandari; Guntur Rambey (Dinasti Review Publisher, 2024)
Amid the development of cellphone penetration, the issue of black market cellphone distribution has become an important part of the telecommunications industry. By selling goods at below-market prices or relatively cheap, which occurs on the black market, most cell phones have unofficial IMEIs. This research aims to find out the legal implementation of smartphone sale and purchase agreements with unregistered or illegal IMEIs. The research method used in this research is the juridical-normative method. This research uses a statutory approach and a conceptual approach from secondary legal materials. The results of his research show that the validity of an illegal smartphone sale and purchase agreement based on the Civil Code is null and void. This is based on the failure to fulfill the legal requirements of the agreement based on Article 1320 of the Civil Code, namely that the object being agreed upon is an unlawful cause. If viewed from the legal aspect of consumer protection, responsibility for buying and selling is regulated in the provisions of Article 19 of Law Number 8 of 1999.